Impact of Artificial Intelligence (AI) Tools on Teaching Effectiveness in Senior Secondary Schools in Gombe State - Musa, Babayo Abdullahi; Usman, Idris; Ibrahim , Bawa; Adamu , Hamza (Kashere Journal of Education, 2025)
This study examines the influence of Artificial Intelligence (AI) tools on teaching effectiveness in senior secondary schools in Gombe State and examines the Impact of AI Tools on Teaching Effectiveness in Senior Secondary Schools in Gombe State. The study adopted a descriptive survey research design. Population of the study was 1,410 Secondary School Teachers in Gombe State, Nigeria; one hundred and seventy-five (175) teachers were used as a sample. Data were collected using a structured questionnaire titled "AI in Education Assessment Scale (AIEAS)". Mean and standard deviation were used to answer the research questions. The reliability of the instrument was established by testing the internal consistency of the items using Cronbach alpha with coefficients ranging from .758 to .879, indicating sufficient internal consistency; the research explored how AI-driven educational technologies enhance lesson delivery, student engagement, assessment, and overall instructional quality. Findings reveal that AI tools significantly improve teachers’ efficiency, enhance personalised learning, and promote data-driven instructional decisions. However, challenges such as limited digital literacy, inadequate infrastructure, and inconsistent internet access hinder optimal utilisation. Recommendations include teacher capacity building, infrastructure development, and supportive policy frameworks.